Proliferative and transcriptional identity of distinct classes of neural precursors in the mammalian olfactory epithelium - Tucker, Eric S. (Company of Biologists, 2010)
Neural precursors in the developing olfactory epithelium (OE) give rise to three major neuronal classes – olfactory receptor (ORNs), vomeronasal (VRNs) and gonadotropin releasing hormone (GnRH) neurons. Nevertheless, the molecular and proliferative identities of these precursors are largely unknown. We characterized two precursor classes in the olfactory epithelium (OE) shortly after it becomes a distinct tissue at midgestation in the mouse: slowly dividing self-renewing precursors that express Meis1/2 at high levels, and rapidly dividing neurogenic precursors that express high levels of Sox2 and Ascl1. Precursors expressing high levels of Meis genes primarily reside in the lateral OE, whereas precursors expressing high levels of Sox2 and Ascl1 primarily reside in the medial OE. Fgf8 maintains these expression signatures and proliferative identities. Using electroporation in the wild-type embryonic OE in vitro as well as Fgf8, Sox2 and Ascl1 mutant mice in vivo, we found that Sox2 dose and Meis1 – independent of Pbx co-factors – regulate Ascl1 expression and the transition from lateral to medial precursor state. Thus, we have identified proliferative characteristics and a dose-dependent transcriptional network that define distinct OE precursors: medial precursors that are most probably transit amplifying neurogenic progenitors for ORNs, VRNs and GnRH neurons, and lateral precursors that include multi-potent self-renewing OE neural stem cells.